Nitella stuartii Braun: A new record of Charophyceae for Bangladesh - Tonne, Nur E Taj Jahan; Ahmed , Tanvir; Alfasane , Md Almujaddade (Bangladesh Journal of Plant Taxonomy, 2024)
Abstract not available Bangladesh J. Plant Taxon. 31(2): 325-327, 2024 (December)